A rule system for translation of universal networking language (UNL)expressions into Armenian - Vahan Avetisyan (Изд-во НАН РА)
In this paper a system of rules is described for automatic translation (deconversion) of Universal Networking Language (UNL) expressions into Armenian sentences.Some classification of rules is proposed for provision of proper coverage of Armenian grammar. Also some approaches to the representation of formalized grammar and morphology of the Armenian Language are described.
Keywords: Mathematics